Impact of Stress on Employee Productivity Performance and Turnover in Nepalese Commercial Banks - Rauniyar, Saroj Kumar (Nepalese Journal of Business, 2025)
This study analyzed the impact of stress on employee productivity performance and turnover in Nepalese commercial banks. The dependent variable selected for the study is employee turnover and employee productivity. Similarly, the selected independent variables are long hour, work life conflicts, job stress, lack of job security, and work overload. The primary source of data is used to assess the opinions of the respondents regarding long hour, work life conflicts, job stress, lack of job security, and work overload in Nepalese commercial banks. The study is based on primary data of 122 respondents. To achieve the purpose of the study, structured questionnaire is prepared. The correlation coefficients and regression models are estimated to test the significance and importance of employee productivity in Nepalese commercial banks. The study shows that long hour is positively correlated to employee turnover. It indicates that higher the long working hour, higher would be the employee turnover. Similarly, work life conflict is positively associated to employee turnover intention indicating that increase in work life conflicts leads to increase in employee turnover. Likewise, job stress is positively correlated to employee turnover indicating that job stress leads to increase in employee turnover. Similarly, job insecurity is positively correlated to employee turnover intention. This implies that higher the job insecurity, higher would be the employee turnover intention. Likewise, work overload is positively correlated to employee turnover intention. This revels that increase in work overload leads to increase in employee turnover intention. The study shows that long hour is positively impact on employee productivity. It indicates that higher the long working hour, higher would be the employee productivity. Similarly, work life conflict is positively associated to employee productivity indicating that increase in work life conflicts leads to increase in employee productivity. Likewise, job stress is positively correlated to employee productivity indicating that job stress leads to increase in employee productivity. Similarly, job insecurity is positively correlated to employee productivity. This implies that higher the job insecurity, higher would be the employee productivity intention. Likewise, work overload is positively correlated to employee productivity intention. This revels that increase in work overload leads to increase in employee productivity.